Ukraine : Accelerating the Transition to Market. (International Monetary Fund, 1997)
Ukraine has made impressive progress in restructuring and stabilizing its economy over the past two years, and yet much remains to be done to revive output and establish a market economy. The 16 papers included in this volume, edited by Peter K. Cornelius and Patrick Lenain, were presented at a seminar sponsored by the IMF and the World Bank in July 1996, which brought together government officials, academics, and staffs of international organizations to discuss a comprehensive medium- term strategy for Ukraine. The papers cover the medium-term macroeconomic framework; wages, poverty, and social safety net reform; private sector development; trade policies and sectoral reforms; and institution building and good governance.